Tuning nonlinear optical absorption properties of WS2 nanosheets. Issue 42 (12th October 2015) - Long, Hui; Tao, Lili; Tang, Chun Yin; Zhou, Bo; Zhao, Yuda; Zeng, Longhui; Yu, Siu Fung; Lau, Shu Ping; Chai, Yang; Tsang, Yuen Hong
Abstract : Size and thickness-dependent nonlinear optical absorption of WS2 is studied. The results indicate that smaller and thinner WS2 exhibit better NOA properties. Abstract : To control the optical properties of two-dimensional (2D) materials is a long-standing goal, being of both fundamental and technological significance. Tuning nonlinear optical absorption (NOA) properties of 2D transition metal dichalcogenides in a cost effective way has emerged as an important research topic because of its possibility to custom design NOA properties, implying enormous applications including optical computers, communications, bioimaging, and so on. In this study, WS2 with different size and thickness distributions was fabricated. The results demonstrate that both NOA onset threshold, F ON, and optical limiting threshold, F OL, of WS2 under the excitation of a nanosecond pulsed laser can be tuned over a wide range by controlling its size and thickness. The F ON and F OL show a rapid decline with the decrease of size and thickness. Due to the edge and quantum confinement effect, WS2 quantum dots (2.35 nm) exhibit the lowest F ON (0.01 J cm −2 ) and F OL (0.062 J cm −2 ) among all the samples, which are comparable to the lowest threshold achieved in graphene based materials, showing great potential as NOA materials with tunable properties.